2010
DOI: 10.1021/jf101220k
|View full text |Cite
|
Sign up to set email alerts
|

Sap Phytochemical Compositions of Some Bananas in Thailand

Abstract: Banana sap has some special properties relating to various phenomena such as browning of fruits after harvesting, permanent staining of cloth and fibers, and antioxidant and antibleeding properties. Analysis of banana sap using high-performance liquid chromatography-electrospray ionization-mass spectrometry (HPLC-ESI-MS) indicated the presence of phenolic and aromatic amino compounds of interest due to their special properties. With the online positive electrospray ionization mode (ESI), the possible structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 30 publications
0
43
0
1
Order By: Relevance
“…Experimental studies have suggested that pseuodostem sap possesses haemostatic and antioxidant properties, has both hyper-and hypoglycemic effects, is diuretic, an antidote for snake bite and cures kidney stones (Singh et al 2007;Pothavorn et al 2010;Prasobh and Revikumar 2011;Weremfo et al 2011;Onyenekwe et al 2013;Ponnambalam and Sellappan 2014). The pseudostem sap can also be used in dyeing cloth, for colour and as a mordant (fixative).…”
Section: Pseudostemmentioning
confidence: 99%
“…Experimental studies have suggested that pseuodostem sap possesses haemostatic and antioxidant properties, has both hyper-and hypoglycemic effects, is diuretic, an antidote for snake bite and cures kidney stones (Singh et al 2007;Pothavorn et al 2010;Prasobh and Revikumar 2011;Weremfo et al 2011;Onyenekwe et al 2013;Ponnambalam and Sellappan 2014). The pseudostem sap can also be used in dyeing cloth, for colour and as a mordant (fixative).…”
Section: Pseudostemmentioning
confidence: 99%
“…56 The presence of flavonoids in root tips of plant grown in light-shield roots suggested that flavonoids are transported from shoot to root. 56 Using fluorescence microscopy, Buer et al (2007) showed that external flavonoids applied to Arabidopsis flavonoid mutants (cannot make flavonoids) accumulates in tissues distal to the application site. 20 In a recent study, many flavonoids were also detected in the phloem sap of banana trees.…”
Section: Flavonoidsmentioning
confidence: 99%
“…55 Recently, it was suggested that flavonoids are transported within plant. 20,56 Flavonoids are not produced in roots grown in complete darkness because expression of genes encoding enzymes of flavonoids biosynthesis is dependent on light. 56 The presence of flavonoids in root tips of plant grown in light-shield roots suggested that flavonoids are transported from shoot to root.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…No research has been reported on the phytochemical screening of banana flowers except a quantitative study on saponin and flavanoid [7] and later phenolic content by Loganayaki et al [8]. The bract part of Musa paradisiaca was reported to contain anthocyanins such as delphinidin, pelaragonidin, peonidin and malvidin [9,10]. Total phenolic content in bract was reported as the lowest compared to other parts such as rhizome, fruit peel, ovary, petiole, pseudo stem and leaves [11].…”
Section: Properties and Applications Of Musa Acuminata Bractmentioning
confidence: 99%